Trimethylamine-N-oxide is elevated in the acute phase after ischaemic stroke and decreases within the first days - Tunkl, Christine; Okun, Jürgen G.; Schwarz, K. V.; Hauke, J.; Zorn, Markus; Nürnberg, Christina; Ungerer, Matthias; Ringleb, Peter A.; Mundiyanapurath, Sibu (European journal of neurology, 2020)
Background and purpose - Trimethylamine-N-oxide (TMAO) is a biomarker of the gut microbiome and correlates with the risk of cardiovascular diseases. However, conflicting data exist on the specific role of TMAO in ischaemic stroke patients.